MicroRNA function in megakaryocytes. (3rd October 2019) - Raghuwanshi, Sanjeev; Dahariya, Swati; Musvi, Syed Shahid; Gutti, Usha; Kandi, Ravinder; Undi, Ram Babu; Sahu, Itishri; Gautam, Dushyant Kumar; Paddibhatla, Indira; Gutti, Ravi Kumar
Abstract: Megakaryocytes (MKs), the largest cells in the bone marrow, are generated from hematopoietic stem cells (HSCs) in a sequential process called megakaryocytopoiesis in which HSCs undergo MK-progenitor (MP) commitment and maturation to terminally differentiated MK. Megakaryocytopoiesis is controlled by a complex network of bone marrow niche factors. Traditionally, the studies on megakaryocytopoiesis were focused on different cytokines, growth factors and transcription factors as the regulators of megakaryocytopoiesis. Over the past two decades many research groups have uncovered the key role of microRNAs (miRNAs) in megakaryocytopoiesis. miRNAs are a class of small length non-coding RNAs which play key regulatory role in cellular processes such as proliferation, differentiation and development and are also known to be involved in disease development. This review summarizes the current state of knowledge of miRNAs which have changed expression during megakaryocytopoiesis, also focuses on miRNAs which are differentially regulated during developmental maturation of MKs. Further, we aimed to discuss potential mechanisms of miRNAs-mediated regulation underlying megakaryocytopoiesis and developmental maturation of MKs.